Study on debugging of lightning impulse voltage waveform for large capacity ±800kV converter transformer in high altitude area - Jiang, Ling; Wang, Shengfu; Kang, Jun; Yang, Xiaoku; Yao, Xiuyuan; Zhang, Yitao; Bao, Zhenghong; Zhang, Yongsheng (Frontiers in Energy Research, 2023)
The Qinghai-Henan ±800kV UHV DC power transmission project is an UHV channel specially constructed for clean energy delivery, ±800kV converter transformers of the project are assembled and tested in Xining at an altitude of 2500m, full-wave lightning impulse test is one of the main means to evaluate converter transformer insulation performance, its valve side lightning impulse voltage waveform parameters often fail to meet IEC60076-3 standards because of the large winding to the ground capacitance. In order to effectively assess the lightning tolerance of converter transformer, a simulation model of impulse test circuit of ±800kV converter transformer was built based on the existing 6000kV/560kJ impulse voltage generator and ATP-EMTP simulation software, three kinds of optimization methods are proposed, which include increasing the wavetail resistance, increasing load capacitor, and connecting the wave head in parallel with different inductors, the results show that the single optimization method can not meet the waveform requirements. Therefore, a combinatorial optimization test method of increasing the wavetail resistance and connecting the wave head in parallel with different inductors is proposed, which is completed and verified in the full-wave lightning impulse test on the valve side of Qinghai ±800kV high-end converter transformer, the results show that the optimized test waveform parameters meet the standard requirements.